WHEN LCA APPLIES TO HEALTH SERVICE INDUSTRY - Djati, Rr. Anggun Paramita; Cahayanti, Sherafina Reni; Chairani, Ellyna; Koestoer, Raldi H.; Hartono, Djoko M. (Journal of Environmental Science and Sustainable Development, 2018)
The health service industry involves activities that provide medical services (hospital), manufacture of medical equipment or drugs, and medical insurance services. Options of research methods to measure the impact of services on environmental aspects are available. One among which is life cycle analysis (LCA), the recently popular practice in Indonesia. This paper attempts to explore whether LCA could be fitted to the health service industry. A literature review would help in procuring related references from various publications accompanied by several research results and related studies. For describing the application of LCA in hospitals, several articles were collected, which were later arranged according to certain systematics from several sources. The LCA methodology used here consists of the following four stages: goal and scope definition, life cycle inventory analysis, impact assessment, and interpretation. The stages follow the International Organization for Standardization (ISO) 14040 and UNEP SETAC, 2011. Several studies using the LCA method in hospitals have reported specific profiles such as the management of biohazardous medical waste (BMW) and waste water. Several studies have also used LCA methods to assess specifically the environmental and health impacts of a specific component of the hospital or hospital activities. For example, studies have assessed the impact of equipment used in the form of containers, catheter, laryngeal mask, gowns and also infrastructures’ facilities. The results of this study confirmed that the LCA method is suitable in health service industry, particularly in hospitals. Considering the merits and drawbacks involved in applying this method, one could further apply it to related health service issues.